Association of duration and etiology with the effect of the artificial liver support system in pediatric acute liver failure - Yang, Chun-Feng; Liu, Jing-Wei; Jin, Lin-Mei; Li, Yu-Mei (Frontiers in Pediatrics, 2022)
Background: We aimed to assess the efficacy of the artificial liver support system (ALSS) in pediatric acute liver failure (PALF) patients and to examine the risk factors associated with the effect of ALSS. Similar data are limited in PALF. Methods: All patients diagnosed with PALF who received ALSS from June 2011 to June 2021 in the pediatric intensive care unit of the First Hospital of Jilin University were included in this retrospective cohort analysis. The effect of ALSS was measured using difference tests before and after treatments. The risk factors associated with the effect of ALSS were evaluated according to whether the total bilirubin (TBIL) and serum ammonia decreased after ALSS (TBIL-unresponsive group vs. TBIL-responsive group, serum ammonia-unresponsive group vs. serum ammonia-responsive group). Results: Thirty-nine patients who received ALSS during the study period were eligible for inclusion. The most common cause of PALF was undetermined causes (n=14, 35.9%) followed by infection (n=11, 28.2%). Four patients received pediatric liver transplantation. The overall survival rate was 76.9% (30/39). Fifteen (38.4%) patients received only one modality, whereas 61.6% patients received hybrid treatments. The most commonly used modality of ALSS was plasma exchange combined with continuous renal replacement therapy (n=14, 35.9%). Alanine aminotransferase, TBIL, the international normalized ratio, and serum ammonia were significantly decreased after ALSS (P<0.001). Compared with other causes, more patients with infection and toxication were observed in the TBIL-unresponsive group. A longer ALSS duration was significantly related to blood ammonia reduction. Conclusions: ALSS can effectively reduce serum alanine aminotransferase, TBIL, international normalized ratio, and serum ammonia and may reduce mortality. The reduction in TBIL levels after ALSS is dependent on etiology. A longer ALSS duration was associated with blood ammonia reduction. Prospective multicenter studies are needed for further validation.